Impact of feeding postbiotics and paraprobiotics produced from Lactiplantibacillus plantarum on colon mucosa microbiota in broiler chickens - Danladi, Yohanna; Loh, Teck Chwen; Foo, Hooi Ling; Akit, Henny; Md Tamrin, Nur Aida; Azizi, Mohammad Naeem (Frontiers Research Foundation, 2022)
This study was conducted to evaluate the impact of feeding postbiotics and paraprobiotics produced from Lactiplantibacillus plantarum on colon mucosa microbiota in broiler chickens. In this study, 336 one-day-old COBB 500 chicks were randomly allotted to eight treatment groups and replicated six times with seven birds per replicate. The treatment included T1 (Negative control) = Basal diet, T2 (Positive control) = Basal diet + 0.01% oxytetracycline, T3 = Basal diet + 0.2% postbiotic TL1, T4 = Basal diet + 0.2% postbiotic RS5, T5 = Basal diet + 0.2% paraprobiotic RG11, T6 = Basal diet + 0.2%postbiotic RI11, T7 = Basal diet + 0.2%paraprobiotic RG14, and T8 = Basal diet + 0.2% paraprobiotic RI11. There were reported changes in the bacterial community using 16S rRNA sequencing of the colon mucosa. The results of the sequencing of 16S rRNA genes in the colon mucosa samples indicated that compared to birds fed the negative control diet, birds fed paraprobiotic RI11 diets were recorded to have a lower relative abundance of Proteobacteria, while those fed the positive control were recorded to have a higher proportion of Firmicutes. Also, lower Enterococcus was reported in paraprobiotic RI11, while the most abundant genus was Bacteroides in postbiotic TL1. This study revealed that supplementation of postbiotics and paraprobiotics in the diets of broilers demonstrated positive effects on the microbiota by supporting the increase of beneficial microbes like the Firmicutes while decreasing harmful microbes like the Proteobacteria. Therefore, this study has provided knowledge on the modification of chicken mucosa microbiota through the feeding of postbiotics and paraprobiotics.